Simplified vacuum dressing system: operational and financial feasibility study in the management of wounds - Sandro Cilindro de Souza; Carlos Maurício Cardeal Mendes; Jose Valber Lima Meneses; Rosana Dias Menezes (Revista Brasileira de Cirurgia Plástica)
Introduction: The high cost of negative pressure wound therapy (NPWT) makes the procedure less accessible in institutions with limited resources. To solve the problem, streamlined vacuum dressings have been proposed, but the usefulness of these devices has been poorly studied. The objective of this work is to evaluate the feasibility (operational and financial) of a simplified vacuum dressing system model (SVDM). Methods: Operational viability was assessed by studying application time and quantity of dressings performed; financial viability, by analyzing the economic costs of dressing changes. Results: Fifty wounds were treated (25 in each group: SVDM x silver hydrofiber). For SVDM, the number of dressings per patient was lower, while the application time was higher. The SVDM showed higher costs. The increase in the expenses associated with the SVDM was related to the average selling price of the product and the number of dressing changes; treatment time and application time of the SVDM did not interfere with costs. In contrast, SVDM costs proved to be below the announced expenses for conventional NPWT. Conclusion: SVDM was considered viable as long as qualified teams perform it and results in few dressing changes (< 3).